Impact of Body Mass Index on Perioperative Outcomes of Endoscopic Pituitary Surgery. Issue 5 (September 2018) - Lee, Yung-Jae; Wong, Anni; Filimonov, Andrey; Sangal, Neel R.; Yeon Chung, Sei; Hsueh, Wayne D.; Baredes, Soly; Eloy, Jean Anderson
Background: Endoscopic pituitary surgery (EPS) is increasingly being used for the treatment of pituitary lesions. Obesity is a growing epidemic in our nation associated with numerous comorbidities known to impact surgical outcomes. We present a multi-institutional database study evaluating the association between body mass index (BMI) and postsurgical outcomes of EPS. Methods: Patients who underwent EPS from 2005 to 2013 were identified from the American College of Surgeons National Surgical Quality Improvement Program database. Preoperative variables, comorbidities, and postoperative outcomes, such as 30-day complications, morbidity, and mortality, were analyzed. Results: A total of 789 patients were analyzed, of which 382 were obese (BMI ≥ 30) (48.4%). No difference in reoperation rate ( P  = .928) or unplanned readmission rates ( P  = .837) was found between the obese versus nonobese group. A higher overall complication rate was observed in the obese group compared to the nonobese counterparts ( P  = .005). However, when separated into surgical complications (3.7% vs 1.5%, P  = .068) and medical complications (7.6% vs 3.9%, P  = .027), only medical complications, specifically pneumonia, remained significantly different. EPS on obese patients was also associated with prolonged operating time (154.8 min vs 141.0 min, P  = .011). Conclusions: EPS may be a safe treatment option for pituitary lesions in the obese population. Although obese patients undergoing EPS are at increased risk of medical complications and prolonged operating times, this did not influence mortality, reoperation, or readmission rate.